Metabolic profiling and pathway analysis in red arillus of Salacca sumatrana demonstrate significant pyruvate, sulfur, and fatty acid metabolisms - Miftahul Huda Fendiyanto; RIZKY DWI SATRIO; DIDI DARMADI (Society for Indonesian Biodiversity, 2020)
Abstract. Fendiyanto MH, Satrio RD, Darmadi D. 2020. Metabolic profiling and pathway analysis in red arillus of Salacca sumatrana demonstrate significant pyruvate, sulfur, and fatty acid metabolisms. Biodiversitas 21: 4361-4368. Salak or snake fruit (Salacca Reinw.; Arecaceae) is a tropical fruit that has high biodiversity in a tropical country such as Indonesia. Several types of salak can be found in Indonesia, one of which is Salacca sumatrana (Becc.) Mogea. Research on profiling metabolites in S. sumatrana has not been conducted. Therefore, the aim of this study was to determine the metabolite profile and pathway analysis in S. sumatrana, especially in red arillus tissue. This research was conducted by the method of gas chromatography-mass spectrometry (GC-MS) and the study of bioinformatics through metabolomics approaches. The results showed that red arillus had metabolites consisting of groups of fatty acids, esters, alcohols, xylene, phenols, etc.. Significant metabolites found were isobutyl acetate, palmitic acid, formic acid, 2-pentanoic acid, ethylic acid, n-hexadecoic acid, hydroxypentanoic acid, etc. There was a tendency that metabolite ethylic acid, identified as C00033 accession, was a key metabolite in either the pyruvate metabolism pathway or sulfur metabolisms with relatively high impact values. Pathway analysis using bioinformatics studies using MetaboAnalyst shows that four of ten pathways detected had a high log-ratio (p)/pathway impact, i.e., pyruvate metabolism, sulfur metabolism, fatty acid biosynthesis, and biosynthesis of unsaturated fatty acids. Thus, pyruvate, sulfur, and fatty acid metabolisms are important pathways in the red arillus of S. sumatrana. This study can be used as a reference in early metabolomic studies on S. sumatrana using GC-MS and the metabolites identified as metabolite markers can be used for plant breeding and biologists to understand the metabolic mechanism of the red arillus tissues from S. sumatrana.